2009
DOI: 10.5993/ajhb.33.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Counseling and Home Telemonitoring: The Weigh By Day Trial

Abstract: Objective: To test the effects of telephone counseling and telemonitoring on weight loss. Methods: A randomized-controlled trial was conducted over 18 months. Participants were assigned to an immediate or delayed-start group. The intervention included a Thin-Link ® home telemonitoring scale and biweekly telephone counseling over 6 months. Results: The immediate group lost significantly more weight relative to the delayed group over the first 6 months (-7.5 versus +1.3 pounds) and at subsequent visits. Conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
5
22
0
Order By: Relevance
“…The overall results are consistent with previous individual efficacy study findings (Eakin et al, 2007;Goode et al, 2012;Jeffery et al, 2003;van Wier et al, 2009van Wier et al, , 2011Van Wormer and Boucher, 2004;Van Wormer et al, 2009;Wilcox et al, 2006;Youngmass et al, 2010). The reductions in body weight, BMI and waist circumference, and the improvements in physical activity, fruit, vegetables, sweetened drinks and takeaway meal consumption are consistent with previous individual studies (Albright et al, 2005; , 2011Van Wormer and Boucher, 2004;Van Wormer et al, 2009;Wilcox et al, 2006;Youngmass et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall results are consistent with previous individual efficacy study findings (Eakin et al, 2007;Goode et al, 2012;Jeffery et al, 2003;van Wier et al, 2009van Wier et al, , 2011Van Wormer and Boucher, 2004;Van Wormer et al, 2009;Wilcox et al, 2006;Youngmass et al, 2010). The reductions in body weight, BMI and waist circumference, and the improvements in physical activity, fruit, vegetables, sweetened drinks and takeaway meal consumption are consistent with previous individual studies (Albright et al, 2005; , 2011Van Wormer and Boucher, 2004;Van Wormer et al, 2009;Wilcox et al, 2006;Youngmass et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The reductions in body weight, BMI and waist circumference, and the improvements in physical activity, fruit, vegetables, sweetened drinks and takeaway meal consumption are consistent with previous individual studies (Albright et al, 2005; , 2011Van Wormer and Boucher, 2004;Van Wormer et al, 2009;Wilcox et al, 2006;Youngmass et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…The technique resulted in statistically significant weight loss of 5.7 lb compared with a nonsignificant gain of 1.0 lb in the control group. More importantly, like the VanWormer, Martinez, Benson, et al (2009) study, the weight loss was sustained for 1 year following the intervention.…”
Section: Resultsmentioning
confidence: 81%
“…VanWormer, Martinez, Benson, et al (2009) randomized a group of participants from a large managed health care organization into an intervention group and 6-month delayed intervention group. The intervention consisted of daily self-weighing (weight was transmitted via Internet to a website), the use of food and activity logbooks, observing a weekly weight chart, and using an action planner and a digital pedometer.…”
Section: Resultsmentioning
confidence: 99%
“…Several randomised controlled trials have investigated the use of telephone-only delivery to target weight loss in patients recruited from primary care settings, including adults with no or very few comorbidities other than overweight or obesity [13][14][15][16][17][18]. These trials have demonstrated the effectiveness of telephone delivery for improvement in diet and physical activity behaviours, and weight loss in a controlled research context.…”
Section: Introductionmentioning
confidence: 99%